Caracterização e aplicação de vermicultura natural e quimicamente modificada na adsorção de azul de metileno - Maia, Francisco Alexis Dantas (2014)
Chemical modification of clays has been extremely studied in the search for improvements of their properties for use in various areas, such as in combating pollution by industrial effluents and dyes. In this work, the vermiculite was chemically modified in two ways, characterized and evaluated the adsorption of methylene blue dye. First was changed with the addition of a surfactant (hexadecyltrimethylammonium bromide, BHTA) making it an organophilic clay and then by adding an acid (HCl) by acid activation. Some analyzes were performed as X-ray fluorescence (FRX), X-ray diffraction (DRX), adsorption isotherms of methylene blue dye, infrared (FTIR) , scanning electron microscopy (SEM), thermal gravimetric analysis and spectroscopy energy dispersive (EDS). Analysis by FRX of natural vermiculite indicates that addition of silicon and aluminum, clay presents in its structure the magnesium, calcium and potassium with 16 % organic matter cations. The DRX analyzes indicated that the organic vermiculite was an insertion of the surfactant in the space between the lamellae, vermiculite and acid partial destruction of the structure with loss of crystallinity. The adsorption isotherms of methylene blue showed that there was a significant improvement in the removal of dye to the vermiculite with the addition of cationic surfactant hexadecyltrimethylammonium bromide and treatment with acid using HCl 2 mol/L. In acid vermiculites subsequently treated with surfactant, the adsorption capacity increased with respect to natural vermiculite, however was much lower compared vermiculite modified with acid and surfactant separately. Only the acidic vermiculite treated with surfactant adjusted to the Langmuir model. As in the infrared spectrometry proved the characteristics of natural vermiculite. In the organic vermiculite was observed the appearance of characteristic bands of CH3, CH2, and (CH3)4N. Already on acid vermiculite, it was realized a partial destruction with decreasing intensity of the characteristic band of vermiculite that is between 1074 and 952 cm-1. In the SEM analysis, it was observed that there was partial destruction to the acid treatment and a cluster is noted between the blades caused by the presence of the surfactant. The TG shows that the higher mass loss occurs at the beginning of the heating caused by the elimination of water absorbed on the surface between layers. In the organic vermiculite also observed a loss of mass between 150 and 300 °C caused decomposition of the alkylammonium molecules (surfactants)